The analysis of cathepsin L that mediates cellular SARS‐CoV‐2 infection leading to COVID‐19 in head and neck squamous cell carcinoma - Gao, Feng; Wang, Xia; Qin, Nianhong; Zhang, Mingxia; Liao, Mingfeng; Zeng, Meiqi; Lu, Desheng; Sha, Ou (Frontiers in Immunology, 2023)
It is well-established that the oral cavity is one of the areas most vulnerable to SARS-CoV-2 infection. Cancer patients reportedly experience a higher incidence of COVID-19, emphasizing the need to prioritize this patient population. Head and neck squamous cell carcinoma (HNSCC) is one of the most common malignant cancers associated with early metastasis and poor prognosis. It has been established that Cathepsin L (CTSL) is expressed by cancerous tissues and encodes a lysosomal cysteine proteinase that regulates cancer progression and SARS-CoV-2 entry. Therefore, it is critical to predict the susceptibility of cancer patients to SARS-CoV-2 and evaluate the correlation between disease outcomes and CTSL expression in cancer tissues. Using transcriptomic and genomic data, we profiled CTSL expression in HNSC in this study and developed a CTSL signature that could reflect the response of HNSCC patients to chemotherapy and immunotherapy. The relationships between CTSL expression and immune cell infiltration were also investigated. We substantiated that CTSL is a potential carcinogenic factor for patients with HNSCC. The findings of this research could help researchers better understand the mechanisms underlying the increased susceptibility of HNSC patients to SARS-CoV-2 infection and lay the groundwork for SARS-CoV-2 therapy.